Dwarf Galaxies: Keys to Galaxy Formation and Evolution: Proceedings of Symposium 3 of JENAM 2010 - Papaderos, Polychronis (Springer Berlin Heidelberg, 2012)
Dwarf galaxy research constitutes an extremely vibrant field of astrophysical research, with many long-standing questions still unsettled and new ones constantly arising. The intriguing diversity of the dwarf galaxy population, observed with advanced ground-based and space-borne observatories over a wide spectral window providing an unprecedented level of detail, poses new challenges for both observers and theoreticians. The aim of this symposium was to bring together these two groups to exchange ideas and new results on the many evolutionary aspects of and open issues concerning dwarf galaxies. The main topics addressed include: the birth of dwarf galaxies: theoretical concepts and observable relics across wavelengths and time, the morphological, structural and chemical evolution of dwarf galaxies, possible evolutionary connections between early-type and late-type dwarfs, the star formation history of dwarf galaxies and its dependence on intrinsic and environmental properties, the origin and implications of starburst activity in dwarf galaxies, the fate of dwarfish systems born out of tidally ejected matter in galaxy collisions.
Includes bibliographical references and indexes
Keywords: Konferenzschrift -- Lissabon #2010; Zwerggalaxie